The use of technology by people with dementia and informal carers during COVID-19: a cross-country comparison. (October 2021) - Chirico, Ilaria; Giebel, Clarissa; Lion, Katarzyna; Mackowiak, Maria; Cations, Monica; Chattat, Rabih; Gabbay, Mark; Moyle, Wendy; Pappadà, Alessandro; Rymaszewska, Joanna; Senczyszyn, Adrianna; Szczesniak, Dorota; et al.
Abstract : Background: Social distancing rules and the closure of services associated with the COVID-19 pandemic have strongly impacted the physical and mental health of people with dementia. Digital technologies can represent an effective means to compensate for the distress associated with social distancing rules and the decreased use of in-person services. More specifically, technologies such as smartphones, tablets, and smart home systems can minimize the negative effects of social distancing and isolation, and the pressure on health and care systems. Indeed, they can provide a continuity of care and social connectedness, while decreasing exposure to risk. However, barriers such as digital literacy and lower income households can impede the access and use of digital technologies. The aim of this international study was to compare the use of technology by people with dementia from different care settings, and their informal carers across four countries (Italy, UK, Australia, and Poland). Methods: People with dementia and informal carers were invited to participate in semi-structured interviews. Verbatim transcripts were analysed by researchers in each country using inductive thematic analysis. Results: A total of 141 people with dementia and carers (47 in Italy; 50 in the UK; 18 in Australia; 26 in Poland) were interviewed. The analysis identified three overarching themes: 1) different uses of technology (three subthemes); 2) benefits of technology (three subthemes); 3) limitations of technology (three subthemes). Results show that calls, video calls, and group-chats were effectively used across countries to guarantee the continuity of relationships with professionals, families, and small groups of peers. Telemedicine was used with varying levels of satisfaction. Furthermore, the benefits experienced by carers exceeded those for people with dementia. Similar barriers were reported across countries, and were strictly associated with dementia deficits, low level digital literacy, and the need for carer's supervision. Conclusions: These international findings highlight the importance to maximise the benefits related to the use of technology according to people with dementia's impairment and care context. Moreover, it should be complementary to in-person care which should be provided, at least to some extent, even during pandemic times.